Republic of Mozambique : Staff Report for the 2015 Article IV Consultation, Fifth Review Under the Policy Support Instrument, Request for Modification of Assessment Criteria, and Request for an 18-Month Arrangement Under the Standby Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Republic of Mozambique. (IMF Staff Country Reports; Country Report ;, 2016)
This 2015 Article IV Consultation highlights that despite lower commodity prices and a weaker global environment, Mozambique's economic prospects remain positive given planned massive investment in natural resources. Although GDP growth averaged 7 percent over the last five years, Mozambique's per-capita income and human development index remain low. There is a need to continue implementing policies that support fiscal sustainability, infrastructure investment, and inclusive growth. Mozambique's economic outlook remains robust. Growth of 6.3 percent is expected in 2015, and remains below potential at 6.5 percent in 2016, mainly owing to a stagnant mining sector and substantially tighter fiscal and monetary policies.